On the Modeling of Spar-type Floating Offshore Wind Turbines - DINH, VAN NGUYEN; BASU, BISWAJIT (My University, 2013)
In this paper an overview about floating offshore wind turbines (FOWT) including operating conditions, property and applicability of the barge, tension-leg, and spar floating platforms is described. The spar-floating offshore wind turbines (S-FOWT) have advantages in deepwater and their preliminary design, numerical modeling tools and integrated modeling are reviewed. Important conclusions about the nacelle and blade motions, tower response, effects of wind and wave loads, overall vibration and power production of the S-FOWT are summarized. Computationally-simplified models with acceptable accuracy are necessary for feasibility and preengineering studies of the FOWT. The design needs modeling and analysis of aero-hydro-servo dynamic coupling of the entire FOWT. This paper also familiarizes authors with FOWT and its configurations and modeling approaches.
PUBLISHED
Keywords: Wind energy; floating offshore wind turbine; spar-type; modeling; coupled analysis.